FENOMENA POLA ASUH ORANGTUA MENGGUNAKAN MEDIA GAWAI PADA ANAK DI KOTA DENPASAR - Ikka Wardhani, Ida Ayu Dea; Punia, I Nengah; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI (SOROT), 2021)
Parenting style is a way for parents to establish child's personality into what is expected by parents. However, current condition makes parents are busy and hard to take care of their children and they use another alternative, that is gadget. This study used descriptive-explorative qualitative research with qualitative data taken through interview, observation and document study. The researcher's aim was to describe the background and the impact of the use of gadget by parents on children in Denpasar city. Researcher have found that the culture of giving gadgets to children is considered commonplace by parents, preoccupation and parental aversion to parenting to be another reason in the upbringing. Both positive and negative effects are springing up and affecting their social behavior. Key words: parents, children, parenting style, gadget